2014
DOI: 10.3748/wjg.v20.i38.14051
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal stem cell therapy for decompensated liver cirrhosis: A meta-analysis

Abstract: BM-MSC infusion in the treatment of decompensated liver cirrhosis improved liver function. At the end of year 1, there were no serious side effects or complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Before MSCs reach clinical application a number of issues must be addressed. Recent meta-analyses have concluded that although no serious side effects or complications have been reported, and therefore MSC therapy may be considered safe, study methodology is in general deficient, making multicenter randomized prospective trials necessary to develop standardized protocols for MSC transplantation (33, 34). Optimal cell dosage, route of administration, number of injections, and therapeutic timing have yet to be determined (35), and the questions of MSC therapy's long-term effectiveness and potential tumorigenic risk have yet to be answered (36).…”
Section: Stem Cellsmentioning
confidence: 99%
“…Before MSCs reach clinical application a number of issues must be addressed. Recent meta-analyses have concluded that although no serious side effects or complications have been reported, and therefore MSC therapy may be considered safe, study methodology is in general deficient, making multicenter randomized prospective trials necessary to develop standardized protocols for MSC transplantation (33, 34). Optimal cell dosage, route of administration, number of injections, and therapeutic timing have yet to be determined (35), and the questions of MSC therapy's long-term effectiveness and potential tumorigenic risk have yet to be answered (36).…”
Section: Stem Cellsmentioning
confidence: 99%
“…Although these stem cells show promise for many potential applications, data on the safety, cell regulation, and ethical aspects is limited (Coradeghini et al, 2010). Therefore, stem cells such as mesenchymal stem cells (MSCs) derived from the bone marrow Stock et al 2010;Pournasr et al 2011;Pan et al 2014), umbilical cord blood (Li et al 2009;Hong et al 2014), and adipose tissue (Al Battah et al 2011;Baer 2011;Cheng et al 2011) can be considered worthy alternatives for ESLD treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Liver transplantation is currently the only definitive therapy for decompensated cirrhosis. However, due to shortcomings such as scarcity of organ donation, high‐operational cost, lack of expertise, and centers that offer liver transplantation services, there is an urgent need to develop alternative therapies . Stem cell infusion therapy is one such alternative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells from the BM give rise to hematopoietic stem cells (HSC) as well as stromal or mesenchymal stem cells (MSC) . Both HSC and MSC therapies have been explored in an experimental manner for both acute and chronic liver injuries, with human BM MSC showing some promise in recent reports …”
Section: Introductionmentioning
confidence: 99%